Competitive Advantage Strategy in Increasing Product Sales in the Health Industry with SWOT Analysis of PT. XYZ - Muhammad Raffi Irfan Gunawan; Hapzi Ali (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
This study aims to analyze and formulate an effective competitive advantage strategy for PT. XYZ in an effort to increase sales of its products in the health industry sector. The method used is SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, which identifies internal strengths, weaknesses, external opportunities, and threats faced by the company. The results of the study revealed that PT. XYZ has advantages in the form of a widely recognized brand, a high level of consumer trust, and a solid distribution network. On the other hand, the Company will face a number of challenges, including dependence on certain superior products and limitations in creating new product innovations. Great opportunities lie in the increasing trend of healthy lifestyles and demand for herbal products, while threats come from new competitors and strict government regulations. Based on this analysis, strategies such as product diversification, quality improvement and innovation, and expansion of domestic and international markets are formulated. This strategy is expected to strengthen PT. XYZ competitive position and encourage sustainable sales growth.